SSPECIES AND POPULATION - Ishmuradova Saboat Narzullayevna (Academia Science Repository, 2023)
Species and population are two ecological classifications of organisms on earth. Species consist of a similar type of individuals who are capable of interbreeding with each other. A population is composed of a group of individuals who live in a certain habitat at a certain time. This is the main difference between species and population.